To determine which equation describes the function in the table, we need to observe the relationship between \(x\) and \(y\).
The given points are:
- When \(x = 0\), \(y = -5\)
- When \(x = 1\), \(y = -9\)
- When \(x = 2\), \(y = -13\)
- When \(x = 3\), \(y = -17\)
Now let's analyze the change in \(y\) as \(x\) increases by 1:
- From \(y = -5\) (at \(x = 0\)) to \(y = -9\) (at \(x = 1\)), the change is \( -9 - (-5) = -4\).
- From \(y = -9\) (at \(x = 1\)) to \(y = -13\) (at \(x = 2\)), the change is \( -13 - (-9) = -4\).
- From \(y = -13\) (at \(x = 2\)) to \(y = -17\) (at \(x = 3\)), the change is \( -17 - (-13) = -4\).
This indicates that for each increase of 1 in \(x\), \(y\) decreases by 4. Thus, the slope of the line is \(-4\).
Starting with the slope-intercept form of a linear function \(y = mx + b\), we can see that \(m = -4\).
Now we need to determine the \(y\)-intercept \(b\). Using the point \((0, -5)\):
- When \(x = 0\), \(y = -5\), which gives us \(b = -5\).
Putting this together gives us the equation: \[ y = -4x - 5 \]
In function notation, this is written as: \[ f(x) = -4x - 5 \]
From the provided options, the correct equation is: f(x) = -4x - 5